Elisabeth Schüssler Fiorenza and the Quest for the Historical Jesus - Walters, Amy Madeleine (Open theology, 2020)
The feminist theological and historical work of Elisabeth Schüssler Fiorenza has been met with diverging responses. For feminist biblical scholars, Schüssler Fiorenza is essential reading, with even her works from the 1970s and 1980s still standing as key reference points. For mainstream ("malestream") biblical scholarship, however, her entire body of writing is typically ignored, including within historical Jesus research (HJR), despite its value in both problematising and advancing the so-called Quests for the Historical Jesus. By evaluating and synthesising Schüssler Fiorenza’s HJR work on fundamentalism, feminism, and anti-Semitism, this article situates the effects of Schüssler Fiorenza’s work and the credibility of her critics within the Quests. While the themes Schüssler Fiorenza addresses, such as feminism and Judaism, are key features of the Third Quest, Schüssler Fiorenza’s proposals with regard to HJR, including the politics of interpretation, the shift to memory and orality studies, and the evaluation of meaning-making itself, are theoretically critical and self-reflexive in a way which the Third Quest has rarely been. Given the emphasis Schüssler Fiorenza places on self-evaluation, and her critical examination of the work of her peers in HJR, one is led to consider the possibility that her work may represent a Third Quest Critical-Stream, or even a Fourth Quest.